(untitled) (Heritage, 2026)
The cultural history of a city is best evidenced by its symbols, traditions and cultural elements that point to the richness of the diversity of cultural symbols that contribute to the uniqueness and originality of an area, in this case the city of Kosovska Mitrovica. The paper examines the cultural life of the city of Kosovska Mitrovica and the main cultural elements that reflect the spirit of the times in the city on the Ibar River. The aim of the paper is to present the rich cultural history of the aforementioned city, imbued with deep social messages that reflect it. In the case of the city of Kosovska Mitrovica, the intertwining of rich tradition and history is explicitly shown, as well as, on the other hand, reflections of the far-reaching consequences of war events during the NATO aggression. The specificity of the city is particularly reflected in the bridge over the Ibar River, which divides the city into southern and northern parts, and all this would not be unique if the bridge in this case did not symbolize the division into two diametrically different social lives, life in a divided city between Serbs and Albanians. Sociologically, the city on the Ibar River represents a unique phenomenon in the world, imbued with a rich cultural and historical heritage, and despite all the challenges it endures and resists time.